Hubungan Pola Asuh Santri Dengan Adab Murid terhadap Guru di Pondok Pesantren Al Falak Pagentongan Bogor - Fani Fadilah; Fahmi Irfani; Nirwan Syafrin (Tarbiatuna: Journal of Islamic Education Studies, 2022)
Adab (ethic/morality) of student toward his teacher is very important so that the knowledge obtained is a blessing and useful. But this blessing and benefit will not be immediately felt. Usually those blessing and benefits will only be realized in the future the knowledge gained being implemented in life. The adab of students bears a direct impact upon the teachers such that it can give a good motivation to the teacher: the teacher will feel good for us, be sincere, and pray good for us. The purpose of this study is to know the relationship between pattern of parenting the students with their ethic or morality towards their teachers in Pondok Pesantren Al Falak. This research is quantitative in nature. The study finds that the pattern of parenting in Pondok Pesantren Al Falak Pagentongan Bogor is inclined more towards authoritarian. This is evident from the number of respondents' answers which opt "a'" (60%), while those who opt for the answer "b" only 17%, the answer "c" is 10%, and the answer "d" is 12%. The study further proves that the pattern of parenting in this Pesantren plays an important role in shaping the ethic of the students in Pondok Pesantren AL Falak Pagentongan Bogor. This is evident from the number of respondents' answers with the answer "a" as much as 75%, the answer "b" as much as 15%, the answer "c" as much as 7%, and the answer "d" as much as 3%. From the calculation rxy of 0.367 numbers the correlation index obtained is not marked negative, which is located between 0.20 - 0.40. Based on the guidelines of the product moment correlation table used, it can be said that between the santri parenting variable (X) and the student adab variable to the teacher (Y) there is a significant relationship, but tends to be low / weak. Keywords: Adab, Parenting, Boarding School